The Norwegian Legislation on Social Sustainability: An Overview of the Transparency Act - Liv Monica Stubholt; Tone Sørfonn Moe; Nina Stærnes (Oslo Law Review)
As the EU awaits the adoption of the proposed Directive on Corporate Sustainability Due Diligence, several European countries have already implemented obligations on human rights due diligence at national level. One of these countries is Norway, where the Transparency Act entered into force in July 2022. The Act serves as one of the frontrunners to the expected EU legislation on social sustainability, largely inspired by international frameworks on business and human rights, as well as other countriesʼ regulations of similar matters. Binding legislation in this area, such as the Transparency Act, is an important development as experience has shown that soft law alone is not enough to efficiently combat human rights violations in global supply chains. This article presents the core obligations and principles of the Transparency Act. The aim of the article is to highlight the distinctive characteristics of the Norwegian Act and reflect on where the road of transparency has lead Norway so far, and where it will lead us next.